DTC of PMSM based on a simple duty ratio approach with ripple reduction scheme - Lemma, Berhanu Deggefa; Pradabane, Srinivasan; Sutikno, Tole; Reta, Getu Girma; Feyisa, Negasa Muleta (International Journal of Power Electronics and Drive Systems (IJPEDS), 2025)
Today, phase permanent magnet synchronous motor (PMSM) applies to electric drives. But due to its structure and control scheme, PMSM suffers from ripple performance when a control scheme like direct torque control (DTC) is used. This work uses a simple scheme to generate switching signals and determine duty ratios. The duty ratio is obtained from the Volt-second balance. Switching signal generation is performed in the DTC scheme by incorporating the effects of duty ratio, torque error, flux error, and sector number. Dwelling time is obtained in volt-seconds using the reference voltage magnitude and sector number. But voltage state selection is done using the DTC lookup table. Since the DTC lookup table is used for voltage state selection only one active and one null voltage is used. Both active and null voltage periods are divided into two parts and each voltage vector is applied twice in one total switching period. The proposed scheme is tested in MATLAB 2021b. Simulation results indicate that the method is effective in terms of dynamics and harmonics. The scheme torque ripple is 12.5%. Likewise, the flux ripple and harmonic are 0.69% and 0.79%, respectively. Additionally, the scheme is effective for both four quadrants and wide-speed operation. Verification of the proposed scheme is done with OPAL-RT (OP4500). The scheme appears to be effective.